CO2 capture using monoethanolamine (MEA) aqueous solution: Modeling and optimization of the solvent regeneration and CO2 desorption process - Mores, Patricia Liliana (2012)
This paper deals with the simultaneously optimization of operating conditions (pressures, temperatures and flow-rates) and dimensions (diameter and height) of the amine regeneration unit in the postcombustion CO2 capture process. The proposed model takes into account the effect of kinetic reactions on the mass transfer, the hydraulics of the random packing and the pressure drop along the column. In addition, profiles of temperature, composition and flow-rate along the height of the regenerator are also predicted. The resulting mathematical model is implemented into the optimization environment General Algebraic Modeling System (GAMS) which is a high-level modeling system for mathematical programming and optimization. The benefits of the mathematical programming techniques (equation-oriented modeling tools) are exploited for the simultaneous optimization not only of the operating conditions but also the dimensions of the all piece of equipments (heat exchangers, regeneration unit, condenser and reboiler). The mathematical model was successfully verified by comparison of the obtained results with published experimental data and simulated solutions obtained by a process simulator (HYSYS). Once validated, the model was used for optimization purpose. Finally, in order to study the effect of the main process parameters on the optimized results a sensitivity analysis is also investigated and discussed in detail.